An empirical relationship to determine lateral seismic response of mid‐rise building frames under influence of soil–structure interaction. (30th October 2012) - Hamid Reza Tabatabaiefar, S.; Fatahi, Behzad; Samali, Bijan
SUMMARY In this study, to determine the elastic and inelastic structural responses of mid‐rise building frames under the influence of soil–structure interaction, three types of mid‐rise moment‐resisting building frames, including 5‐storey, 10‐storey and 15‐storey buildings are selected. In addition, three soil types with the shear wave velocities less than 600 m/s, representing soil classes Ce, De and Ee according to AS 1170.4–2007 (Earthquake action in Australia, Australian Standards), having three bedrock depths of 10 m, 20 m and 30 m are adopted. The structural sections are designed after conducting nonlinear time history analysis, on the basis of both elastic method and inelastic procedure considering elastic‐perfectly plastic behaviour of structural elements. The frame sections are modelled and analysed, employing finite difference method adopting FLAC2D software under two different boundary conditions: (a) fixed base (no soil–structure interaction) and (b) considering soil–structure interaction. Fully nonlinear dynamic analyses under the influence of different earthquake records are conducted, and the results in terms of the maximum lateral displacements and base shears for the above mentioned boundary conditions for both elastic and inelastic behaviours of the structural models are obtained, compared and discussed. With the results, a comprehensive empirical relationship is proposed to determine the lateral displacements of the mid‐rise moment‐resisting building frames under earthquake and the influence of soil–structure interaction. Copyright © 2012 John Wiley & Sons, Ltd.